CONCEPTUAL METAPHOR FOR SUMMER IN ENGLISH AND VIETNAMESE SONG LYRICS (Journal of Foreign Language Studies, 2020)
This study aims to identify English conceptual metaphors expressed in English and Vietnamese lyrics based on the theory of conceptual metaphors introduced by Lakoff and Johnson in 1980. The data were collected from 304 English and Vietnamese songs (156 and 148 songs respectively) from the 20th century to the present on the basis of Steen’s (1999) procedure for metaphor identification. This descriptive-comparative study identifies 20 conceptual metaphors expressing summer, 10 of which are similar in the two languages. The study also reveals the similarities and differences between English and Vietnamese metaphors of summer, and then provides explanations for them from the cultural aspects, including people’s living experiences and environment.
Keywords: metaphorical expression; conceptual metaphor; target domain; source domain; mapping